ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK ANTARA PT BANK RAKYAT INDONESIA (PERSERO) TBK DAN BANGKOK BANK MENGGUNAKAN NPL, ROE DAN CAR PERIODE TAHUN 2016-2020 - Eka Sari; Diah Aryati P (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study was to analyze the comparison of bank health levels between PT Bank Rakyat Indonesia (Persero) Tbk and Bangkok Bank using the RGEC method for the period 2016-2020. The results showed that in peride 2016-2020 as a whole using non-performing loan (NPL), return on equity (ROE), and capital adecuancy ratio (CAR) ratio of PT Bank Rakyat Indonesia (Persero) Tbk in 2016-2018 has a very healthy composite rating of 1 with a value weight of 93.33% in 2019 there was a decrease then the composite rating 1 is very healthy with a value weight of 86.67% and in 2020 there was a decrease again. then the composite rating of 2 is healthy with a value weight of 80%. Bangkok Bank in 2016-2020 survived the composite rating of 2 healthy predicates, in 2016-2019 with a value weight of 80% in 2020 there was a decrease in the value of weights to 73.33%. The decline of both banks was caused by a decrease in the value of roe ratio. Based on the assessment, it can be concluded that the performance of PT Bank Rakyat Indonesia (Persero) Tbk during the period 2016-2020 is better than the performance of Bangkok Bank. Both banks are expected to raise profits and greater equity.